The Volcano-Tectonics of the Northern Sector of Ischia Island Caldera (Southern Italy): Resurgence, Subsidence and Earthquakes - Carlino, Stefano; Sbrana, Alessandro; Pino, Nicola Alessandro; Marianelli, Paola; Pasquini, Giuseppe; De Martino, Prospero; De Novellis, Vincenzo (Frontiers in Earth Science, 2022)
The island of Ischia, an active volcanic field emerging in the western sector of the Gulf of Naples (Southern Italy), represents an archetypal case of caldera that underwent a very large resurgence related to the intrusion of a shallow magma body. The resurgence culminated with the formation of a structural high in the central sector of the island, i.e., the Mt. Epomeo block, bordered by a system of faults along which volcanic activity occurred up to 1302 A.D. and damaging earthquakes were generated in historical and recent time. The seismicity is located prevalently in the northern sector of the island and appears to be correlated with the most recent phase of inversion of the ground movement (subsidence), although the mechanism of earthquakes’ generation is still debated. By jointly analyzing offshore and onshore data (seismic profile and stratigraphy wells, respectively) and new petrological and geochemical data related to the most recent phase of volcano-tectonic activity, we develop a geological and structural layout of the northern sector of the island. In particular, we identify a local horst-graben structure, formed in the northern sector of the island in the final stage of the resurgence and including the main seismogenic fault associated with the historical and recent destructive earthquakes of Ischia. A final conceptual volcano-tectonic model of the northern sector of the Ischia Island, depicting the mechanism of stress loading and release in this area and independent on the process driving the subsidence, is also presented. Our results are crucial for evaluating the cinematic of the seismogenic fault as well as the seismic hazard of Ischia. We suggest that, as long as the subsidence will operate, the potential for damaging earthquakes remains high.